Doxorubicin versus doxorubicin and cisplatin in endometrial carcinoma: definitive results of a randomised study (55872) by the EORTC Gynaecological Cancer Group - Aapro, MS (2008)
BACKGROUND: Combination chemotherapy yields better response rates which do not always lead to a survival advantage. The aim of this study was to investigate whether the reported differences in the efficacy and toxicity of monotherapy with doxorubicin (DOX) versus combination therapy with cisplatin (CDDP) in endometrial adenocarcinoma lead to significant advantage in favour of the combination. PATIENTS AND METHODS: Eligible patients had histologically-proven advanced and/or recurrent endometrial adenocarcinoma and were chemo-naïve. Treatment consisted of either DOX 60 mg/m(2) alone or CDDP 50 mg/m2 added to DOX 60 mg/m2, every 4 weeks. RESULTS: A total of 177 patients were entered and median follow-up is 7.1 years. The combination DOX-CDDP was more toxic than DOX alone. Haematological toxicity consisted mainly of white blood cell toxicity grade 3 and 4 (55% versus 30%). Non-haematological toxicity consisted mainly of grade 3 and 4 alopecia (72% versus 65%) and nausea/vomiting (36 % versus 12%). The combination DOX-CDDP provided a significantly higher response rate than single agent DOX (P <0.001). Thirty-nine patients (43%) responded on DOX-CDDP [13 complete responses (CRs) and 26 partial responses (PRs)], versus 15 patients (17%) on DOX alone (8 CR and 7 PR). The median overall survival (OS) was 9 months in the DOX-CDDP arm versus 7 months in the DOX alone arm (Wilcoxon P = 0.0654). Regression analysis showed that WHO performance status was statistically significant as a prognostic factor for survival, and stratifying for this factor, treatment effect reaches significance (hazard ratio = 1.46, 95% confidence interval 1.05-2.03, P = 0.024). CONCLUSIONS: In comparison to single agent DOX, the combination of DOX-CDDP results in higher but acceptable toxicity. The response rate produced is significantly higher, and a modest survival benefit is achieved with this combination regimen, especially in patients with a good performance status.